Yahoo Web Search

  1. Sort by

  1. P = F/(F+U) P(F+U) =F PF+PU=F PF-F=-PU F(P-1)=-PU F=-PU/(P-1) F=PU/(1-P) .....

    1 Answers · Science & Mathematics · 19/10/2013

  2. the sum of the interior angles in a triangle is 180° in a quadrilateral draw a diagonal and get 2 triangles: the sum is 180°×2 = 360° in a pentagon draw two diagonal from the same vertex getting 3 trangles: the sum is 180°×3 = 540° in a polygon with n vertex draw all the...

    1 Answers · Science & Mathematics · 14/09/2013

  3. 1. sup(C)=max(sup(A),sup(B)) Pf: Let t=max(sup(A),sup(B)). If s is greater...

    2 Answers · Science & Mathematics · 11/09/2013

  4. A. The horizontal asymptote will the limit as x goes to ±infinity of (2x+1)/(1-7). That is what you wanted, right? Don't be lazy and leave out the parentheses, since what you wrote can be interpreted a number of...

    1 Answers · Science & Mathematics · 06/09/2013

  5. ...2πm² p is the unknown, so you just multiply by x on each side : pF = p/kp = 1/k and divide by F pF/F = p = 1/kF in a...

    4 Answers · Science & Mathematics · 25/08/2013

  6. You can try to test out with CLEP or DANTES tests. I know, for example, that the DANTES intro to Stats test is easier than the typical course. You have to find out, of course, if your 2-year school will accept two of the courses...

    1 Answers · Science & Mathematics · 28/08/2013

  7. 17) The question needs to be clearer. If a is a constant, then the answer is b). 12) True because 2^x>0. Lim x→-∞ =1 8) c) Because the constant term shifts the graph vertically. 5) d) logx + logy = logxy (Log laws). 3*4=12

    2 Answers · Science & Mathematics · 19/08/2013

  8. ...of wire and wire has resistance). We can get phase angle from power factor. pf = cos θ = 0.90 θ = arccos (pf) = arccos (0.9) = 25.84° lagging...

    2 Answers · Science & Mathematics · 22/08/2013

  9. ... example, for m=2, [1][1]=[1] and [1] is the only non-zero element pf Z/2Z. Therefore, Z/2Z is a field...

    1 Answers · Science & Mathematics · 03/08/2013

  10. LCD = pqf fq + pf = pq f(q+p) = pq f = pq/(q+p)

    2 Answers · Science & Mathematics · 26/07/2013

  1. Try asking your question on Yahoo Answers